A review of Brucea javanica: metabolites, pharmacology and clinical application - Chen, Jing; Yu, Dongke; Li, Xinyu; Deng, Qichuan; Yang, Hao; Chen, Lu; Bai, Lan (Frontiers in Pharmacology, 2024)
This review examines advances in the metabolites, pharmacological research, and therapeutic applications of the medicinal fruit of Brucea javanica (L.) Merr. Brucea javanica (BJ) is derived from the fruit of the Brucea javanica (L.) Merr.. There are nearly 200 metabolites present in BJ, and due to the diversity of its metabolites, BJ has a wide range of pharmacological effects. The traditional pharmacological effects of BJ include antidysentery, anti-malaria, etc. The research investigating the contemporary pharmacological impacts of BJ mainly focuses on its anti-tumor properties. In the article, the strong monomeric metabolites among these pharmacological effects were preliminarily screened.Regarding the pharmacological mechanism of action, current research has initially explored BJ's pharmacological agent and molecular signaling pathways. However, a comprehensive system has yet to be established. BJ preparations have been utilized in clinical settings and have demonstrated effectiveness. Nevertheless, clinical research is primarily limited to observational studies, and there is a need for higher-quality research evidence to support its clinical application. There are still many difficulties and obstacles in studying BJ. However, it is indisputable that BJ is a botanical drugs with significant potential for application, and it is expected to have broader global usage.